EXPLORING THE LINK BETWEEN GREEN FINANCE AND ENVIRONMENTAL IMPROVEMENTS IN COIMBATORE’S MANUFACTURING SECTOR - J. Radhika; K. R. Sivabagyam (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the adoption of green financing initiatives and their impact on sustainable practices and environmental outcomes in manufacturing companies in Coimbatore District. Green financing, encompassing instruments such as green bonds and sustainability-linked loans, has emerged as a critical tool for funding eco-friendly projects. Despite Tamil Nadu’s strong industrial presence and policy emphasis on sustainability, barriers such as limited awareness and technical expertise hinder the effective implementation of green financing in the region. The research adopts a descriptive design, employing a purposive sampling technique to target senior-level employees in the manufacturing sector. A sample size of 137 respondents was selected, and primary data were collected through structured questionnaires. Analytical tools including descriptive statistics, ANOVA, correlation analysis, and multiple regression were used to evaluate relationships between company characteristics, green financing initiatives, sustainable practices, and environmental outcomes. Findings reveal that medium-sized companies (50–250 employees) and organizations operating for less than five years are most represented. ANOVA results demonstrate significant relationships between company characteristics and sustainability dimensions. Correlation analysis highlights a strong positive relationship between sustainable practices and environmental outcomes (r = 0.610, p = 0.000). Regression analysis confirms that 39.3% of the variance in environmental impact is explained by green financing and sustainable practices, with the latter having a stronger influence. Suggestions include enhancing internal mechanisms such as employee training and strategic alignment, prioritizing renewable energy and sustainable supply chains, and pursuing eco-certifications. The study concludes that integrating green financing with operational strategies can drive sustainability and improve environmental performance, aligning Coimbatore’s industrial growth with global sustainability goals.